Organization of the tactical preparation in greco-roman wrestling in the juvenile category - a proposal - Ibanez Diaz, R. E.; Noriega Gómez, J. C. (International Journal of Wrestling Science, 2022)
In this investigation a proposal is made for the organization of the tactical preparation in Greco-Roman wrestling for youth. It has three phases; diagnosis, organization and evaluation of the process. We worked with the team of the youth category of the provincial Sports Initiation School [Escuelas de Iniciación Deportivas Escolares, EIDE] of Villa Clara, for its implementation different methods were used, such as document review, interview, observation, systemic approach, modeling and; historical-logical and inductive-deductive methods. The organization of the treatment of tactical preparation in youth wrestlers of the Greco-Roman style, guaranteed the increase in the state of competitive performance of the wrestlers during the different moments of the preparation cycles, causing the increase in sports results. From its application it was found that the level of tactical effectiveness was raised in the fighters of the youth category of the Greco-Roman style achieving 100% effectiveness in medals, since the four athletes who participated in the Youth Olympiad achieved one gold, one silver and two bronze medals.